BLENDED LEARNING DALAM PENINGKATAN KEMAMPUAN BERPIKIR KREATIF PADA MAHASISWA - Annisah, Siti; Aryanti, Zusy; Wildaniati, Yunita; Wahyuni, Sri (PD PGMI se Indonesia, 2022)
Learning models that are only applied to face-to-face or online learning do not place students in learning situations anytime and anywhere. A conducive learning situation is important to design, especially in improving creative thinking skills, which include high-level abilities. The purpose of this paper is to describe how the blended learning model is able to provide wide space and opportunities for students to be actively involved in learning so as to foster creative thinking skills in problem solving. This research is an experimental study involving only one group. Data collection techniques used are tests, observations, and documentation. The research data were analyzed using the Wilcoxon test. The findings of this study are that 1) the blended learning model is proven to be effective in improving students' creative thinking skills, and 2) student involvement in learning has a positive impact on increasing creative thinking skills. Thus, blended learning learning designs that place students in learning situations without limitations of space and time are considered more effective in improving creative thinking skills